The Equivalence of Two Open Therapeutic Regimens of Cimetidine in the Treatment of Acute Duodenal Ulcer Disease: A Canadian Multicentre Trial - H Navert; AP Archambault; IGM Cleator; NB Hershfield; EJ Prokipchuk; ABR Thomson (Canadian Journal of Gastroenterology)
One hundred and four patients completed a multicentre study comparing the standard cimetidine regimen of 300 mg qid with cimetidine 600 mg bid in the treatment of acute duodenal ulcer. Both dosage regimens were effective in alleviating symptoms. At the two- and four-week assessments a significantly greater decrease in frequency, duration and severity of night time pain was recorded in the 600 mg bid group (P<0.05). The healing rates were equivalent in both treatment groups. After eight weeks of treatment, 96% of the patients had healed in each treatment group. Cimetidine 600 mg bid may represent a useful alternative therapeutic regimen to the standard 300 mg qid dosage in patients with symptomatic acute duodenal ulcer disease.